Robert Michels — zapoznany klasyk socjologii - Miński, Radomir (Kultura i Społeczeństwo, 2017)
Robert Michels (1876–1936) considered himself to be a disillusioned socialist, who, under the influence of elitism, rejected democracy and moved into the fascist camp. As a figure in sociology he is associated solely with the “iron law of oligarchy.” In Poland, it is a little-known fact that in Western social thought he is viewed as a socially engaged sociologist—a “genuine” researcher gifted with sociological imagination and a passion for scholarship. The aim of the author is to present Michels as a scholar in many areas: feminist issues, local patriotism in the context of national citizenship, phenomena of a general sociological nature, the history of Italy, and social movements. Furthermore, the author illustrates the German writer Timm Genett’s thesis that Michels should also be valued as a pioneer in the study of social movements, which he consistently examined in his analyses of organizations, systematically investigating the degeneration of social movements and the shifting of organizational aims.